Glutathione Enhances Antibiotic Efficiency and Effectiveness of DNase I in Disrupting Pseudomonas aeruginosa Biofilms While Also Inhibiting Pyocyanin Activity, Thus Facilitating Restoration of Cell Enzymatic Activity, Confluence and Viability - Das, Theerthankar; Simone, Martin; Ibugo, Amaye I.; Witting, Paul K.; Manefield, Mike; Manos, Jim (Frontiers in Microbiology, 2017)
Pyocyanin secreted by Pseudomonas aeruginosa is a virulence factor that damages epithelial cells during infection through the action of reactive oxygen species, however little is known about its direct effect on biofilms. We demonstrated that pyocyanin-producing P. aeruginosa strains (PA14WT, DKN370, AES-1R and AES-2) formed robust biofilms in contrast to the poorly-formed biofilms of the pyocyanin mutant PA14ΔphzA-G and the low pyocyanin producer AES-1M. Addition of DNase I and reduced glutathione (GSH) significantly reduced biofilm biomass of pyocyanin-producing strains (P < 0.05) compared to non-pyocyanin producers. Subsequently we showed that a combined treatment (CT) comprising: GSH + DNase I + antibiotic, disrupted and reduced biofilm biomass up to 90% in CF isolates AES-1R, AES-2, LESB58 and LES431 and promoted lung epithelial cell (A549) recovery and growth. We also showed that exogenously added GSH restored A549 epithelial cell glutathione reductase (GRed) activity in the presence of pyocyanin through recycling of GSSG to GSH and consequently increased total intracellular GSH levels, inhibiting oxidative stress, and facilitating cell growth and confluence. These outcomes indicate that GSH has multiple roles in facilitating a return to normal epithelial cell growth after insult by pyocyanin. With increased antibiotic resistance in many bacterial species, there is an urgency to establish novel antimicrobial agents. GSH is able to rapidly and comprehensively destroy P. aeruginosa associated biofilms while at a same time assisting in the recovery of host cells and re-growth of damaged tissue.